Leveraging Real-World Evidence to Define Severe RSV Lower Respiratory Tract Disease in Adults - Catherine A. Panozzo; Edward E. Walsh; Zhen Yang; Eleanor Wilson; Jaya Goswami; Sonia K. Stoszek; Adrianna Loback; Tony Ng; Beverly M. Francis; Alana K. Simorellis; Wenmei Huang; Linwei Li; et al. (Infectious Diseases and Therapy)
Abstract Introduction As no standard case definitions for respiratory syncytial virus—associated lower respiratory tract disease (RSV-LRTD) in adults are available, this study analyzed definitions for severe RSV-LRTD from previously published data in hospital and community cohorts of adults with RSV–associated symptoms. Methods The frequency, sensitivity, and specificity of acute respiratory disease symptoms among hospitalized and community cohorts of adults with RSV were analyzed. RSV-LRTD signs/symptoms assessed included shortness of breath (dyspnea), cough and/or fever, wheezing/rales/rhonchi (abnormal lung sounds by auscultation), sputum production, tachypnea, hypoxemia, and pleuritic chest pain. Results Dyspnea and tachypnea provided the best differentiation between hospitalized and community RSV-positive cases. The severe RSV-LRTD case definition yielding one of the highest and best-balanced sensitivity and specificity was dyspnea paired with either abnormal lung sounds by auscultation, hypoxemia, tachypnea, cough and/or fever, sputum, or chest pain. Conclusions Dyspnea alone, and in combination with certain other lower respiratory tract disease signs/symptoms, was a leading symptomatic indicator for severe RSV outcomes. These results contribute to the harmonization of case definitions for RSV disease.